2002
DOI: 10.1590/s0103-50532002000500023
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of L-amino Acids on Sea Sand

Abstract: Foi realizado um estudo da adsorção de L-alanina, L-tirosina, L-ácido glutâmico e L-lisina em areia do mar. Somente L-lisina adsorveu na areia do mar, provavelmente devido à sua cadeia lateral que é positivamente carregada. Portanto, estes resultados apontam dúvidas sobre a importância de areia para a pré-concentração de aminoácidos antes condensação de peptídeos na Terra primitiva.A study of adsorption of L-alanine, L-tyrosine, L-glutamic acid, and L-lysine on sea sand was carried out. Only L-lysine showed ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
6

Year Published

2004
2004
2013
2013

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 14 publications
1
22
0
6
Order By: Relevance
“…Bernal 1951 was the first that suggested that minerals could be played an important role in the adsorption of key monomers from dilute solution and their subsequent condensation to form biopolymers. Besides some doubts about the role of minerals in the processes of selection of monomers (Zaia et al 2002, Zaia 2004, Benetoli et al 2007, Benetoli et al 2008, adsorption of biomolecules on minerals is an important issue in prebiotic chemistry (Lambert, 2008). In the present work, the adsorption of adenine on bentonite and montmorillonite with and without preadsorbed sulfide was studied at different pH (2.00, 7.00).…”
Section: Efficient Synthesis Of Pyrimidines and Triazines From Urea Amentioning
confidence: 98%
“…Bernal 1951 was the first that suggested that minerals could be played an important role in the adsorption of key monomers from dilute solution and their subsequent condensation to form biopolymers. Besides some doubts about the role of minerals in the processes of selection of monomers (Zaia et al 2002, Zaia 2004, Benetoli et al 2007, Benetoli et al 2008, adsorption of biomolecules on minerals is an important issue in prebiotic chemistry (Lambert, 2008). In the present work, the adsorption of adenine on bentonite and montmorillonite with and without preadsorbed sulfide was studied at different pH (2.00, 7.00).…”
Section: Efficient Synthesis Of Pyrimidines and Triazines From Urea Amentioning
confidence: 98%
“…Mellersh e Wilkinson 31 verificaram que o ácido poliadenílico liga-se à sílica gel e que, de um pool de 18 aminoácidos, somente L-lisina e L-arginina (ambos com grupos R positivamente carregados) ligaram-se no sistema constituído por sílica/ácido poliadenílico. Zaia et al 32 realizaram um estudo da adsorção da alanina (grupo R não polar alifático), tirosina (grupo R aromático polar em pH alto), ácido glutâmico (grupo R negativamente carregado) e lisina (grupo R positivamente carregado) sobre areia do mar, observando que somente a lisina adsorveu em uma quantidade apreciável sobre esta areia. Churchill et al 33 utilizaram a técnica de microscopia de força atômica (AFM) para medir o ponto de carga zero (pH pzc ) de diversos minerais (quartzo, calcita, sílica de vidro e albita).…”
Section: Adsorção De Aminoácidos Sobre Mineraisunclassified
“…Entretanto, os resultados acima apresentados, levaram Zaia et al 32 e Zaia 34 a proporem algumas questões sobre o papel dos minerais na pré-concentração dos aminoácidos. Klapper 35 publicou um estudo sobre a composição de aminoácidos em mais de 200 proteí-nas.…”
Section: Adsorção De Aminoácidos Sobre Minerais Foi Importante Para Aunclassified
See 2 more Smart Citations